The Role of Fiqh Learning Assistance in Improving Students’ Awareness of Performing Prayer at TPQ Mafatihul Huda - Ani Tuti Aswati; Errina Usman (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2025)
This study aims to describe the role of Fiqh learning assistance in improving students’ awareness of performing prayer at TPQ Mafatihul Huda. The research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. The participants included mentors, teachers, and TPQ students. The findings reveal that Fiqh learning assistance plays a significant role in enhancing students’ understanding and awareness of prayer obligations. Through interactive teaching approaches, teacher role modeling, and practical worship activities, students showed positive changes in discipline and motivation to perform prayers. Therefore, Fiqh learning assistance is proven effective in fostering students’ religious awareness and consistent worship behavior.